IDENTIFIKASI DAN PENILAIAN RISIKO PADA PROYEK PEMBANGUNAN PERUMAHAN DAMARA VILLAGE JIMBARAN - I GUSTI AGUNG AYU ISTRI LESTARI; I GEDE ANGGA DIPUTERA; NI PUTU MONIKA ARIESTY (Universitas Mahasaraswati K. Mataram, 2023)
Considering the implementation of the large and extensive Damara Village Housing Development project with an area of 3.5 hectares and a total of 169 units, there are potential risks that could occur during the project's execution. This thesis was conducted using a qualitative approach (interviews) which will be quantified or described using numerical data or the descriptive method. The stages involved conducting interviews with various parties, namely 25 respondents who are experts and have competence in Damara Village Housing, to determine the likelihood of various risks, assess the magnitude of the risks' consequences, and evaluate the risks. Risk assessment is the result of multiplying the likelihood of risk by its consequences. The research findings indicate that there are 36 identified risks, of which 3 (8.3%) are classified as unacceptable risks, 32 (88.9%) are undesirable risks, 1 (2.85%) is an acceptable risk, and 0% or no risk falls under the negligible category